Islam and Muslims in the West - Duderija, Adis. author. aut Link
VIII, 259 p.
Keywords: This book analyzes the development of Islam and Muslim communities in the West, including influences from abroad, relations with the state and society, and internal community dynamics. The project examines the emergence of Islam in the West in relation to the place of Muslim communities as part of the social fabric of Western societies. It provides an overview of the major issues and debates that have arisen over the last three to four decades surrounding the presence of new Muslim communities residing in Western liberal democracies. As such, the volume is an ideal text for courses focusing on Islam and Muslim communities in the West. Adis Duderija is Lecturer in the Study of Islam and Society in the School of Languages and Social Science, Griffith University, Australia. Halim Rane is Associate Professor of Islam-West Relations in the School of Humanities, Languages and Social Science, Griffith University, Australia.